The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.chroma.2010.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Changes in solvent exposure reveal the kinetics and equilibria of adsorbed protein unfolding in hydrophobic interaction chromatography

Abstract: Hydrogen exchange has been a useful technique for studying the conformational state of proteins, both in bulk solution and at interfaces, for several decades. Here, we propose a physically-based model of simultaneous protein adsorption, unfolding and hydrogen exchange in HIC. An accompanying experimental protocol, utilizing mass spectrometry to quantify deuterium labeling, enables the determination of both the equilibrium partitioning between conformational states and pseudo-first order rate constants for fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Proteins may change their native conformation upon binding to HIC surfaces . This phenomenon has been studied for modern HIC media by use of deuterium exchange, circular dichroism, spectroscopic techniques, and isocratic elution techniques . McCue et al.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…Proteins may change their native conformation upon binding to HIC surfaces . This phenomenon has been studied for modern HIC media by use of deuterium exchange, circular dichroism, spectroscopic techniques, and isocratic elution techniques . McCue et al.…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…Among the goals of predictive methods is identifying the conditions where target proteins would be sufficiently stable during HIC. While there is evidence that resins of higher hydrophobicity destabilize proteins more than those of lesser hydrophobicity [13][14][15], no generalized empirical or theoretical framework exists to identify the resins and the mobile phase conditions that can destabilize a protein.…”
Section: Background and Introductionmentioning
confidence: 97%
“…It is known that (NH 4 ) 2 SO 4 binds water strongly; raising the concentration of the salt decreases charge shielding, promotes exposure of the hydrophobic patches both in the molecules and on the stationary phase, results in increased hydrophobic affinity between the molecules and the stationary phase, and promotes the unfolding of proteins from their native state. [11] A recent study on the structure of BSA molecules absorbed on AuNRs with synchrotron radiation X-ray absorption spectroscopy and molecular dynamics simulations showed that the proteins undergo only partial spreading after AuNR binding, and that their structural flexibility is preserved, thus implying that they can still respond to the local environment change. [12] Hence, although the protein-coated AuNRs are quite large, their interfacial behavior is similar to that of proteins alone, so they can be treated as large artificial semielastic molecules for the purpose of protein-surface interaction studies.…”
mentioning
confidence: 99%